Pemberdayaan Masyarakat dalam Mengembangkan Wisata Air Terjun Batu Dinding Kabupaten Kampar - Syafri Harto; Ismandianto Ismandianto; Belli Nasution (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Empowerment is an effort to provide or strengthening to the community. Community empowerment activities in Tanjung Belit Village, Kampar Regency, university service programs in the development of regional tourism in Indonesia. The community service program in collaboration with real work lectures (KKN) aims to improve community welfare by utilizing information technology in the tourism sector. The method of implementing the service program is carried out by socializing the improvement of community human resources, utilizing technology, and practice as well as collaborating with the community in carrying out tourism development programs. The results of this activity are 1) Increasing human resources (HR) in the tourism sector for rural communities through social technology, 2) Fostering community creativity in processing juaro fish catches into processed fish balls. 3) Increasing public knowledge about the use of narrow land with the Budikdamber method. 4) aware of the importance of protecting forest ecosystems.